Peran Dan Kontribusi Ismail Al-Faruqi Terhadap Gerakan Angkatan Belia Islam Malaysia - Ahmad Nabil Amir; Tasnim Abdul Rahman (EL-EMIR Institute, 2026)
This research is motivated by the importance of understanding the influence of contemporary Islamic thought on the modern da'wah movement, particularly the contribution of Ismail Raji al-Faruqi in shaping the direction of the Angkatan Belia Islam Malaysia (ABIM) movement. The urgency of this research lies in the need to examine the relationship between the idea of ​​the Islamization of knowledge and the practice of Islamic movements at the organizational level, especially in facing the challenges of modernity and the identity crisis of the younger generation of Muslims. This study aims to analyze the role and contribution of al-Faruqi's thought to the development of ABIM. The method used is a qualitative approach with a type of library research, through data collection from relevant primary and secondary sources. Data analysis was conducted descriptively-analytical with a historical and conceptual approach. The results of the study indicate that al-Faruqi's thought contributed significantly to shaping the Islamic paradigm of ABIM, particularly in the fields of education, da'wah, and youth development, through the integration of the values ​​of monotheism and science.